Study of the environmental parameters of the parasitic plant Cistanche tubulosa L. and its relationship Some of his host plants - Widad M. Al-Asadi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The environmental criteria and the rates of infection for plant parasite Cistanche tubulosa (Schenk) R. Wight of Orobanchaceae on some of the plants hosts ( Hammada salicornia (Moq.) Iljin. (Syn: Haloxylon salicornicum)  Tetraena propinqua (Decne.) Ghaz. & Osborne (Zygophyllum propinquum)   propinqua  (Decne.) Ghaz. & Osborne which are considered the main hosts in Iraq were determined in this study. The study was carried out in the areas of plant spread in southern Basra governorate (Khadr al-Mai, Jrishan, Jwaibdh, Safwan and Jabal Sanam).It was found that the rate of infection of the first type is higher than the second type, and the maximum biomass of the plants studied was the parasite plant compared with host plants, whether infected or uninfected and mentioned to environmental limits C. tubulosa and its relation to the studied species.It was observed that the highest density and the highest percentage of frequency were for the parasite species in the Griishan followed by the Khadr al-Mai, and also recorded the maximum percentage of the important value,  and the result Showed that the strongest correlation between the studied species was between C. tubulosa and H. Salicornia.